2016
DOI: 10.1155/2016/4602751
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Seasonal Gastrointestinal Parasitic Infections in Donkeys from a Semiarid Sub-Saharan Region, Sudan

Abstract: Out of 92 donkeys examined for gastrointestinal parasites, 90 animals were found infected by one or more gastrointestinal parasites with an overall prevalence rate of 97.78%. The distributions of the recovered parasites in the different parts of the body were as follows: stomach, 92.4%, small intestine, 19.6%, caecum, 88%, colon, 80.4%, rectum, 73.9%, and cranial mesenteric artery, 64.1%. A significant difference was found between mean parasite counts and seasons. Hot wet season had higher mean parasites count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…In a research carried out by Ahmed et al [6] in Egypt, 98.45% of the donkeys sampled were infected by helminths and 22 species were identified. is is also similar to the study by Ismail et al [7] who found an almost similar overall prevalence. Matthee et al [8] identified 15 genera and 29 species of helminths in seven donkeys necropsied in South Africa, with Strongylus vulgaris being the most abundant and prevalent strongyle species.…”
Section: Introductionsupporting
confidence: 92%
“…In a research carried out by Ahmed et al [6] in Egypt, 98.45% of the donkeys sampled were infected by helminths and 22 species were identified. is is also similar to the study by Ismail et al [7] who found an almost similar overall prevalence. Matthee et al [8] identified 15 genera and 29 species of helminths in seven donkeys necropsied in South Africa, with Strongylus vulgaris being the most abundant and prevalent strongyle species.…”
Section: Introductionsupporting
confidence: 92%
“…Different pattern of genera composition and proportions of large and small strongyle infections have been reported in donkeys in different geographical areas. In Africa, a high prevalence of both large and small strongyles was generally found in donkeys infected by intestinal strongyles [36][37][38]. In recent studies in donkeys in Egypt and Sudan [36,38] a high prevalence of both small strongyles (cyathostomins, 72.3 to 90%) and large strongyles (84%), including S. vulgaris (16.7-60%), S. equinus (22-30%), and S. edentatus (18-30%), were observed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Yoseph et al [15], Fikru et al [16], Gizachew et al [17], Ayele et al [13] and Berhanu et al [18] and Ismail et al [19] reported prevalence between 97% -100%. The current lower prevalence compared to the previous reports was due to the regular deworming habit of the cart horse owners, as 139 (36.2%) of the equines examined had deworming history.…”
Section: Discussionmentioning
confidence: 99%